Current State of Minimal Invasive Surgery for Intracranial Epidural Hematoma - Fitra, Fitra; Meizikri, Rizki; Wathoni, Roidah TZ; Hidayat, Imam (Journal of International Surgery and Clinical Medicine, 2024)
Introduction Craniotomy and hematoma evacuation is the gold standard of treatment for epidural hematoma (EDH). However, minimal invasive surgery for EDH might come in handy in conjunction or as a standalone therapy for EDH, as some of them might be easier to perform in a dire situation. In this literature review, we aim to review the available literatures regarding minimally invasive surgery for EDH. Method This literature review described the available studies about minimal invasive surgery for EDH. Result Thirteen studies were identified. The procedures consisted of burrhole-based approach, minicraniotomy, endovascular, and image-guided evacuation. Several of the procedures were performed on hypodense-appearing EDH, some on post-operative EDH, and one on venous-sinus-involving EDH. The majority of studies reported favourable outcome after minimal invasive surgery. Conclusion Available literatures showed that most minimal invasive surgery can be performed quickly and is thus suitable for the emergency nature of EDH. Liquified-appearing EDH, post-operative EDH, or EDH situated near the dural venous sinus were among the reasons to pursue minimal invasive EDH evacuation. Minimal invasive surgery for EDH generally resulted in favourable outcome. Larger studies are required to validate the benefit of minimal invasive surgery as a standalone therapy or in combination with standard craniotomy for EDH.